Crowdinvesting in entrepreneurial projects: Disentangling patterns of investor behavior - Maximilian Goethner; Sebastian Luettig; Tobias Regner (Friedrich Schiller University Jena, 2018)
Crowdinvesting emerged recently as an alternative way of funding for start-up projects. Our dataset consists of all pledges made at Companisto, one of the largest crowdinvesting platforms in Europe. Using cluster analysis based on individual investment histories, we find that crowdinvestors differ in their investment strategies and motivations. We can distinguish three types of crowdinvestors that vary in their response to project quality signals of entrepreneurs, project-related information reducing the degree of uncertainty and social influence by fellow investors: Casual Investors, Crowd Enthusiasts, and Sophisticated Investors. We conclude that crowdinvestors are anything but a homogeneous group. Instead, they are motivated by different factors and respond to different signals when making investment decisions.
Keywords: G23; G41; L26; 330; Crowdinvesting; Entrepreneurial finance; New ventures; Cluster analysis; Social influence; Signaling